2020
DOI: 10.1097/meg.0000000000001853
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis E virus in Argentinean blood donors

Abstract: Background Hepatitis E virus (HEV) is the main cause of enteric acute viral hepatitis worldwide. In this epidemiological framework, it has become a threat to blood safety and a relevant issue for blood transfusions. However, there is a paucity of data regarding prevalence of HEV infection. The aim of this study was to determine HEV seroprevalence in blood donors from different regions from Argentina. Material and methods Serum samples from 391 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Studies of HEV PCR positivity rates of blood donors worldwide [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]; Table S2. Studies of HEV seroprevalence of blood donors worldwide [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70...…”
unclassified
“…Studies of HEV PCR positivity rates of blood donors worldwide [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]; Table S2. Studies of HEV seroprevalence of blood donors worldwide [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70...…”
unclassified
“…This genotype was previously found in environmental, swine, and human samples from Argentina. 7 , 13 , 14 , 29 In this study, HEV RNA was detected in 11 clinical cases, including four pregnant women and one immunosuppressed man. Despite none of these patients developed severe liver disease, the immunosuppressed patient presented HEV RNA positivity for a longer period, perhaps acting as a viral reservoir and a possible source of transmission.…”
Section: Discussionmentioning
confidence: 74%
“…Studies have demonstrated HEV antibody prevalence from 5.1 to 20.0% in different regions of Argentina. 7 , 8 , 9 Regarding hepatitis A, prevalence rates ranged from 29.7% in Buenos Aires 2 to 81.9% in low-income indigenous populations. 9 …”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the operation of the plant is altered by clandestine connections of home storm drains to the sewerage network. Furthermore, the stormwater drainage network, which includes piped streams, is affected by clandestine connections of industrial and sewage effluents ( 18 ). On the opposite, in the low-risk spatial cluster flooding events are unusual and people live more distant to water courses.…”
Section: Discussionmentioning
confidence: 99%
“…In the central region, Córdoba city (Argentina), the overall IgG anti-HEV prevalence obtained in blood donors ( n = 547) was 3.47% ( 17 ). Di Lello et al ( 18 ) conducted a study in blood donors ( n = 391) of five Argentinian regions and found that HEV seropositivity varied from 5.1 to 20.0%.…”
Section: Introductionmentioning
confidence: 99%